Analytical modelling of tantalum/titanium oxide‐based multi‐layer selector to eliminate sneak path current in RRAM arrays. Issue 7 (27th October 2020) - Lekshmi Jagath, Arya; Kumar, Thulasiraman Nandha; Almurib, Haider Abbas; Jinesh, Kochupurackal Balakrishna Pillai
Abstract : One selector‐one resistor (1S‐1R) configuration is desirable to use in conductive bridge resistive random‐access memory (CBRAM) and resistive random‐access memory (RRAM) crossbar arrays (CBAs) to reduce sneak path current. In this study, an analytical model of Ta2O5/TaOx/TiO2 selector device is developed and is integrated with RRAM model to demonstrate the acquired features of 1S‐1R to reduce the sneak path current. The proposed selector model is developed by considering the electric field‐driven tunnelling mechanisms co‐exist in thin multi‐layer devices such as direct and Fowler‐Nordheim tunnelling. The simulated characteristics of proposed model shows high non‐linearity (∼1600), high selectivity (∼10 4 ), high current density (∼10 7 A/cm 2 ) and low off current (∼46 nA). Further, the proposed model is simulated with different top electrode metals and dielectric materials to demonstrate the formation of optimal stack for the desired application. Then, the proposed selector model (1S) is integrated with RRAM model (1R) and the compatibility of the devices is verified. Moreover, from the presented 1S‐1R model, various parameters for the establishment of CBA such as read/write voltages for selected/unselected trails are predicted and substantial conditions for sneak path current reduction such as non‐linearity, Roff/Ron ratio and off‐current (10 nA) are also evaluated.